PENYALAHGUNAAN WEWENANG JABATAN OLEH PEJABAT NEGARA/PEMERINTAH : PERSPEKTIF HUKUM ADMINISTRASI NEGARA DAN HUKUM PIDANA - Sobirin Malian (Jurnal Hukum Respublica, 2020)
On November, 17, 2019, it was reported that the President Director of PT Garuda Indonesia Tbk. I Gusti Ngurah Askhara (Ari Askhara) got involved in the illegal Harley Davidson motorcycle parts and Brompton bikes found in the Garuda Indonesia aircraft. He was fired from the position. The case of the illegal spare parts by the Customs and Excise officers on the Airbus A330-900 Neo aircraft with the flight number GA 9721 on Sunday November, 17, 2019 is one more abuse of power among so many similar cases done by state officers. The case proves that an official power is vulnerable to corrupt. Abuse of power is as old as the age of human civilization. Abuse of power is an unlawful act done by a person or people in an official capacity. Abuse of power breaks the article 3 of the Indonesian Law No. 31 Year 1999 jo the Indonesian Law No. 20 Year 2001, that is “Anybody who with the intention to earn profit for himself or another person or a corporation, abuses the authority, opportunity or facilities given to him on account of his post or position which may cause loss to the state finance or state economy, shall be sentenced to life imprisonment or a minimum sentence of 1 (one) year and a maximum of 20 (twenty years) or a minimum fine of ..." It is a qualitative research methodology with observation and literary review to collect data. The research concludes that state administration officials should have professionally technical skills and morality to do their duties. If they do not have them, they might be fired in the perspective of administrative law and be sentenced to life imprisonment in the perspective of criminal law.